Stress and coping strategies in the general population of Greece and Cyprus in response to the COVID-19 pandemic: A cross-sectional study - Kleanthous, Efrosyni; Evangelou, Efi; Georgiadou, Andri; Galanis, Petros; Andreadaki, Evangelia; Tzavara, Chara K.; Kaitelidou, Daphne Ch; Kallergis, Georgios E. (My University, 2023)
The COVID-19 pandemic and the lockdown policy had a profound psychological impact on the general population worldwide. The aim of this study was to assess the level of stress and coping strategies used during the initial stage of the COVID-19 outbreak and their association. Secondary aims were to a) identify the most important coping strategies and b) investigate predictors of stress. A cross-sectional study was conducted by using an anonymous online questionnaire. The study was carried out from April 23 to May 4 2020. A snowball sampling method was conducted to recruit potential participants from the general population of Greece and Cyprus. Participants over 18 years old who were familiar with the Greek language were included. The psychological impact was assessed by the Impact of Event Scale-Revised (IES-R). Coping strategies were assessed using 15 statements detected from a review of the literature. Participants were asked to rate each one of the coping strategies according to how important it was to them, on a four-point likert scale. The sample consisted of 3941 participants (74.2% women, N=2926), with a mean age of 36.9 years old. The most important coping strategies adopted were 1) "Dealing the situation with a positive attitude" (96.5%), 2) "Follow strict personal protective measures" (95,9%), 3) "Acquiring knowledge about coronavirus" (94.6%), 4) "Engaging in health-promoting behaviors" (89.6%), 5) "Limiting the time spent on media" (75.5%). The highest and positive coefficients were recorded for the association of IES-R scales with 1) "Talking with family and friends to reduce stress", 2) "Seeking help from a mental health professional", 3) "Limiting the time spent on media", 4) "Relieving and managing emotions", 5) "Practicing relaxation techniques". 26.5% showed severe psychological impact. Conclusion: Addressing stress levels with the use of functional coping strategies can be beneficial to protect the general population from adverse psychological outcomes.
Keywords: COVID-19; Coping strategies; Cross-sectional studies; Stress disorders; traumatic